Elasto-viscous regime in coalescence of viscoelastic droplets - Pallavi Katre; Bimalendu Mahapatra; Manaswita Karmakar; Sarang Jagdish; Navin Kumar Chandra; Aloke Kumar (Proceedings of the National Academy of Sciences, 2026)
The merging of two droplets represents an energy-minimizing process whereby they combine to produce a thermodynamically stable droplet. Coalescence of Newtonian droplets is characterized by distinct viscous and inertial regimes. In contrast, viscoelastic fluids containing polymers display additional regimes when elastic and viscous stresses are comparable. We reveal a transition from an elasticity-dominated regime to an elasto-viscous regime in the coalescence of concentrated polymer droplets. Experimental measurements of interface curvature reveal that common assumptions used to estimate axial curvature are not universal. Using numerical simulations based on a volume-of-fluid framework with the exponential Phan–Thien–Tanner model, we reproduce the viscoelastic neck growth in good agreement with experiments. These results advance the understanding of droplet coalescence and highlight the role of viscoelastic effects in complex fluids.